2020
DOI: 10.3390/cells9010214
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Quality Control: Role in Cardiac Models of Lethal Ischemia-Reperfusion Injury

Abstract: The current standard of care for acute myocardial infarction or ‘heart attack’ is timely restoration of blood flow to the ischemic region of the heart. While reperfusion is essential for the salvage of ischemic myocardium, re-introduction of blood flow paradoxically kills (rather than rescues) a population of previously ischemic cardiomyocytes—a phenomenon referred to as ‘lethal myocardial ischemia-reperfusion (IR) injury’. There is long-standing and exhaustive evidence that mitochondria are at the nexus of le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 347 publications
(615 reference statements)
0
31
0
Order By: Relevance
“…The aforementioned energetic breakdown of the cell provokes a mitochondrial depolarization and the closing of mitochondrial permeability transition pore (MPTP), which is accompanied by increases in lactate, succinate and other ROS precursors associated in this oxygen deprivation condition. In this sense, mitochondrial protection conferred by PEG35 would be a critical point in ischemias, as recently suggested by Kulek et al [48] With its potential cytoprotective effects in mind, we evaluated the benefits of PEG35 in rinse solution for graft washout after cold preservation [19]. The presence of PEG35 in rinse solution after static preservation in UW confirmed that this polymer is directly responsible for mitochondrial preservation during cold storage, including as well the concomitant activation of cytoprotective factors such as AMP-activated protein kinase (AMPK) and presumably the inherent cytoskeleton rearrangement [19].…”
Section: Static Cold Storage (Scs) and Pegmentioning
confidence: 61%
See 1 more Smart Citation
“…The aforementioned energetic breakdown of the cell provokes a mitochondrial depolarization and the closing of mitochondrial permeability transition pore (MPTP), which is accompanied by increases in lactate, succinate and other ROS precursors associated in this oxygen deprivation condition. In this sense, mitochondrial protection conferred by PEG35 would be a critical point in ischemias, as recently suggested by Kulek et al [48] With its potential cytoprotective effects in mind, we evaluated the benefits of PEG35 in rinse solution for graft washout after cold preservation [19]. The presence of PEG35 in rinse solution after static preservation in UW confirmed that this polymer is directly responsible for mitochondrial preservation during cold storage, including as well the concomitant activation of cytoprotective factors such as AMP-activated protein kinase (AMPK) and presumably the inherent cytoskeleton rearrangement [19].…”
Section: Static Cold Storage (Scs) and Pegmentioning
confidence: 61%
“…The aforementioned energetic breakdown of the cell provokes a mitochondrial depolarization and the closing of mitochondrial permeability transition pore (MPTP), which is accompanied by increases in lactate, succinate and other ROS precursors associated in this oxygen deprivation condition. In this sense, mitochondrial protection conferred by PEG35 would be a critical point in ischemias, as recently suggested by Kulek et al [ 48 ]…”
Section: Static Cold Storage (Scs) and Pegmentioning
confidence: 72%
“…The important role of mitochondrial quality control mechanisms (involving the regulation of the mitochondrial fission and fusion, proteolysis and mitophagy) in the responses to H/R stress is well established in the hypoxia-sensitive mammalian models such as rodents (Kulek et al, 2020;Wang and Zhou, 2020). Earlier studies also indicate that high activity and upregulated mRNA expression of mitochondrial proteases correlates with elevated hypoxia tolerance in marine bivalves .…”
Section: Introductionmentioning
confidence: 99%
“…Pathological cardiac conditions resulting from ischemic cardiac injuries and occlusion of a coronary vessel induces a cascade of tissue hypoxia and cellular ATP depletion ( Peoples et al, 2019 ). A series of events may contribute to this process of ischemic and reperfusion damage to cardiac tissues with impairment of mitochondrial integrity being central to this process, including the generation of ROS, opening of the mitochondrial permeability transition pore (mPTP), and activation of intrinsic apoptosis ( Kulek et al, 2020 ). Under these drastic changes in nutrient and oxygen availabilities, a decrease in oxidative phosphorylation results in a decrease in cellular ATP, and a loss of mitochondrial membrane potential ( Murphy and Steenbergen, 2008 ).…”
Section: Association Of Cardiovascular Diseases and Mitochondrial Dysmentioning
confidence: 99%